Impact of Vocational Training for Women Empowerment - Gautam, Susmita (Academic View, Journal of TUTA Tri-Chandra Campus Unit, 2023)
Vocational training involves acquiring specific skills and knowledge, turning individuals into skill-based workers capable of generating income through their expertise. This study, titled "Impact of Vocational Training for Women Empowerment," aimed to explore whether such training programs contribute to women’s social and economic independence. Additionally, the research sought to understand the reasons behind women opting for skill-based work and whether these trainings lead to positive changes in their lives. The study delved into various aspects related to women, the challenges hindering their development and growth, as well as national and international policies concerning women and informal workers. It particularly focused on the current situation of skill-based female workers in Mahankal Rural Municipality, Lalitpur district. The study discovered that through vocational training women are enabled and can meet the individual prerequisites of themselves and other relatives since they approach the right to family decision-making, financial opportunity, and freedom. This demonstrates how the achievement of Sustainable Development Goal 5, which primarily focuses on achieving gender equality and women’s empowerment, has been helped along by the development of vocational skills.